Whose fault? Defendant perceptions of their own blameworthiness and guilty plea decisions - Lee, Jacqueline G. (Journal of crime and justice, 2024)
With the present paper, we seek to understand how defendants form of perceptions blameworthiness and to assess how these perceptions affect willingness to accept a plea offer. With an online vignette survey (N = 659), we randomized 1) guilt and 2) riskiness of victim behavior in a vehicular manslaughter case. We also asked respondents to rate the blameworthiness of themselves and their victims. First, results indicate that guilty respondents were more likely to accept a plea than those who were innocent. Second, those in the low-risk victim behavior condition viewed themselves as more blameworthy. Third, people who view themselves as more blameworthy, or their victims as less blameworthy, are more likely to take a plea offer. Lastly, the effects of guilt, victim behavior, and perceptions of victim blameworthiness are also at least partially mediated by perceptions of self-blame. Overall, victim behavior was a key predictor of self-blameworthiness, which was then a critical predictor of WTAP. Results also suggest that respondents viewed blame as a zero-sum game and made decisions about whether to accept a plea based on whether they think they were at fault in the situation.